Pemodelan Kasus Kekerasan Terhadap Perempuan di Jawa Barat: Poisson dan Negatif Binomial - Ramadhan, Aditya Rifqi; Al-Husein, Fulkan Kafilah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Violence against women is a complex social issue with widespread impacts. West Java was recorded as the province with the highest number of cases in Indonesia in 2023, with various factors such as poverty, unemployment, and human development suspected to influence its prevalence. This study aims to model the number of cases of violence against women using Poisson and negative binomial regression to identify significant factors affecting the case numbers. The data were obtained from secondary sources, covering 27 regencies/cities in West Java. The analysis indicates that the Poisson regression model is unsuitable due to overdispersion, while the negative binomial regression model successfully addresses this issue with a lower AIC value. The results suggest that the number of people living in poverty has a significant influence on the prevalence of violence against women. This study provides valuable insights for data-driven policy-making efforts to reduce cases of violence against women and improve social welfare.